High division of sciatic nerve - Shrivastava, Tripti; Garg, Lalit; Mishra, B. K.; Chhabra, Neeta (International Journal of Research in Medical Sciences, 2017)
Background: The Sciatic nerve is the largest and thickest nerve in the human body with a long course in the inferior extremity. It divides into tibial and common peroneal nerves which can occur at any level from the sacral plexus to the inferior part of the popliteal space. Sciatic nerve variations are relatively common. These variations may contribute to clinical conditions ex sciatica, coccygodynia and piriformis syndrome and have important clinical implications in anaesthesiology, neurology, sports medicine and surgery. Methods:10 cadavers were dissected with no previous history of trauma/surgery to study the anatomical variations of sciatic nerve. Results:In all except two cadavers, the nerve divided at the apex of the popliteal fossa. In two cadavers the sciatic nerve divided bilaterally in the upper part of thigh. Conclusion: The high division presented in this study can make popliteal nerve blocks partially ineffective. The high division of sciatic nerve must always be borne in mind as they have important clinical implications.